BUDAYA “KAWIN KYAI” Studi Terhadap Praktek Nikah Sirri Di Desa Sinarrancang, Kecamatan Mundu, Kabupaten Cirebon - Farabi, Al (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2011)
Regulation about the registration of marriage has been around a long time. Active role of the state in aspect of registration of marriage started early independence. That role was confirmed by the Act. No. 1 of 1974 on Marriage and regulations for its implementation which requires every registration of marriage for the sake of order and legal certainty. However, in the village of Cirebon Sinarrancang Mundu are 59, 35 % of the 246 families who do not heed the regulation that marry with only religious well-known as